Colombia’s potential for trade with the European Union and other major global markets - Jaime Rafael Ahcar Olmos (CEPAL Review, 2018)
This paper identifies potential for trade between Colombia and the European Union following the implementation of a free trade agreement as from 2013. Predictions of potential are based on estimates produced by the Poisson pseudo maximum likelihood estimator applied to a gravity model, controlling for unobserved omitted variable bias with exporter and importer time-varying fixed effects on a sample of 153 countries, from 1980 to 2012. Untapped potential is found in both directions of trade flows. The results could increase the effectiveness of trade policy and define companies’ expansion plans in international markets.